Ti-oxo radicals and product selectivity in olefin oxidations over titanosilicate molecular sieves - Shetti, VN; Srinivas, D; Ratnasamy, P (Zeitschrift für Physikalische Chemie International Journal of Research in Physical Chemistry and Chemical Physics, 2005)
The O-O bond of Ti-oxo species (Ti-peroxo, Ti-hydroperoxo or Ti-superoxo) generated on titanosilicate molecular sieves contacted with H2O2 cleaves either heterolytically or homolytically. While the former type of O-O cleavage (generating non-radical reactive oxygen intermediates) leads to selective epoxide products, the latter (generating reactive oxygen radical intermediates, O-2(-center dot) and HOOcenter dot) results in non-sclective, allylic oxidation products in cyclohexene oxidation. These radicals were detected using EPR spin trapping techniques 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) was used as the spin trap. Radical quenchers like hydroquinone suppressed their concentration and enhanced epoxide selectivity.
Keywords: cyclic voltammetry of titanosilicates; EPR-spin trap experiments; Molecular sieves; oxidations; product selectivity; reactive oxygen species; titaniunz-oxo radicals; Titanosilicates